2021
DOI: 10.1002/casp.2523
|View full text |Cite
|
Sign up to set email alerts
|

Testing social identity models of collective action in an Iranian environmental movement

Abstract: The social identity model of collective action (SIMCA) and the encapsulation model of the social identity of collective action (EMSICA) are well‐known models that have been applied to protest action. The current study tests the predictive value of the core constructs in the models (social identification, perceived injustice and group efficacy) in a peaceful pro‐environmental program. Specifically, we sought to answer whether the two models provide equally good accounts of (self‐reported) past participation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 49 publications
(64 reference statements)
1
11
0
Order By: Relevance
“…However, the time referent of the action measure (i.e., self-reported actions taken in the past year) was implicit in the re-contacting of participants annually but was not explicit. Moreover, some recent research has found that the predictors of intentions to act and self-reported (past) behavior can differ (Keshavarzi et al, 2021). Reflecting on past action is not the same as feeling motivated to act in the present, and therefore it may be that different solutions will be obtained where intention to act is modeled instead of self-reported action.…”
Section: Discussionmentioning
confidence: 99%
“…However, the time referent of the action measure (i.e., self-reported actions taken in the past year) was implicit in the re-contacting of participants annually but was not explicit. Moreover, some recent research has found that the predictors of intentions to act and self-reported (past) behavior can differ (Keshavarzi et al, 2021). Reflecting on past action is not the same as feeling motivated to act in the present, and therefore it may be that different solutions will be obtained where intention to act is modeled instead of self-reported action.…”
Section: Discussionmentioning
confidence: 99%
“…That is, through collective action tendencies that would enhance the ingroup situation (Wright et al, 1990). Importantly, following previous research, we also consider the collective action antecedents, namely social support and group efficacy perceptions (see e.g., Keshavarzi et al, 2021;Ochoa et a., 2019;Saab et al, 2015;Van Zomeren et al, 2004, 2008, in order to better understand participants' reactions towards the group disadvantage. Therefore, we test the internal legitimacy effect and the reliability of that norm on social support, group efficacy, and collective action tendencies against the disadvantage.…”
Section: The Present Researchmentioning
confidence: 99%
“…Considering that civic engagement and collective action are the main means to advocate for political, civil, social, and human rights (Arcidiacono, Natale, Carbone, & Procentese, 2017; Chan, Cattaneo, Mak, & Lin, 2017; Furlong & Vignoles, 2021; Keshavarzi, McGarty, & Khajehnoori, 2021; Mazzoni, van Zomeren, & Cicognani, 2015), research on the factors that promote immigrants' engagement in collective action and other forms of voice seems socially and heuristically relevant. This is all the more so as there is evidence that they face more barriers than nonimmigrant groups in engaging in various forms of participation (Martinez Damia et al, 2020).…”
Section: Introductionmentioning
confidence: 99%